Caribbean Report 15-06-1995 - Ransome, Debbie (anchor); Simmonds, Kennedy (interviewee); Douglas, Denzil (interviewee); Richards, Ken (correspondent); Smith, Lew (correspondent); Spencer, Baldwin (interviewee); Arnold, Thomas, Sir (interviewee); Baldry, Tony (interviewee) (The British Broadcasting Corporation, 1995)
This report highlights the impending elections in St. Kitts/Nevis on July 3rd. Prime Minister Kennedy Simmonds and Opposition Labour Party, Denzil Douglas talk about their campaign agenda. Dominica's new Prime Minister Edison James finalizes his Cabinet and adopts the foreign affairs portfolio. Meanwhile, the two opposition parties have resolved the impasse regarding the Leader of the Opposition. In Grenada, Lew Smith examines the three major political parties manifestos. On the agenda of the meeting of LIAT Directors is the issue of share allocation for the airline and Trinidad's proposal for the removal of LIAT's Chairman William Rapier. In the British Parliament, Sir Thomas Arnold comments on Britain's policy towards the Caribbean. The majority of businesses in downtown Kingston closed in to protest the rising crime. A team from the Inter-American Dialogue, a Washington based think-tank, made its first visit to Cuba and met with government officials as well as non-governmental organizations and dissident groups. Cuba states that it has not offered to extradite American fugitive Robert Vesco.
1. Headlines with Debbie Ransome (00:00-00:29)
2. An election date of July 3rd has been announced in St. Kitts/Nevis (00:30-04:31)
3. Dominica's new Prime Minister takes on the foreign affairs portfolio and selects new Ministers for the Cabinet (04:32-06:14)
4. Lew Smith examines the manifestoes of the three main political parties in Grenada (06:15-08:46)
Keywords: Saint Kitts and Nevis -- Politics and government; Elections -- Saint Kitts and Nevis; Dominica -- Politics and government; Political leadership -- Dominica; Civil service positions -- Dominica; Grenada -- Politics and government; Political manifestoes -- Grenada; Political parties -- Grenada; Airlines -- Caribbean Area; Airlines -- Management -- Trinidad and Tobago; Stocks; Great Britain -- Foreign relations -- Caribbean Area; Caribbean Area -- Foreign relations -- Great Britain; Non-self-governing territories; Business enterprises -- Jamaica; Violent crimes -- Jamaica; Crime -- Social aspects -- Jamaica; United States -- Foreign relations -- Cuba; Cuba -- Foreign relations -- United States; Fugitives from justice -- United States